2022
DOI: 10.3390/ma15051623
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Graphene Oxide on the Properties and Microstructure of Clay-Cement Composite Grouting Materials

Abstract: Reductions in bleeding rates and bulk shrinkage of grouting repair materials comprise the key to solving the leakage of earth–rock dams. In this paper, an anti-seepage grouting material for earth–rock dam was developed by introducing mineral admixtures and graphene oxide (GO) nano sheets into low-cost clay–cement grouting materials and by adding polycarboxylate superplasticizers (PCs) to improve slurry viscosity. The experimental results show that the shear stress and viscosity of the slurry increase with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The platelet structure enables it to physically intercept crack growth at the nano level in addition to the pore filling effect, unlike 0D nanomaterials such as nanosilica, which has only a filling effect at the physical level. Because of the abundance of the hydrophilic functional groups on the GO’s basal planes, it is easier to disperse in the mix, enhancing its effectiveness, unlike 1D nanomaterials such as carbon nanotubes, whose high interparticle cohesive force hinder proper dispersion [ 26 ]. These advantages make GO a popular choice in the nanomodification of cementitious composites, with encouraging reported findings.…”
Section: Introductionmentioning
confidence: 99%
“…The platelet structure enables it to physically intercept crack growth at the nano level in addition to the pore filling effect, unlike 0D nanomaterials such as nanosilica, which has only a filling effect at the physical level. Because of the abundance of the hydrophilic functional groups on the GO’s basal planes, it is easier to disperse in the mix, enhancing its effectiveness, unlike 1D nanomaterials such as carbon nanotubes, whose high interparticle cohesive force hinder proper dispersion [ 26 ]. These advantages make GO a popular choice in the nanomodification of cementitious composites, with encouraging reported findings.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low cost, it is now widely used to improve grout performance and reduce costs. Herath et al [9] mentioned that mineral admixtures can replace 20% to 35% of cement in equal amounts to formulate grout under the premise of improving the performance of grout. Vasumithran et al [10] conducted indoor tests based on cement-based grout composed of silica fume, fly ash, and fine sand, and they found that the particle size of the constituent materials was one of the most important influencing factors for the viscosity of the grout samples and that the grout with the addition of mineral admixtures was more viscous.…”
Section: Introductionmentioning
confidence: 99%